Implementation of a complete systematic land registration policy at the Malinau District Defense Office - Syamsi, Ardiyan (Trigin Publisher, 2023)
This study aims to analyze the implementation of PTSL policies along with the factors that influence the implementation of these policies. This research uses qualitative methods, data in this study was obtained by conducting in-depth interviews, observations and documentation. Data collection techniques use interview methods to find out more in-depth things about participants, observation to obtain actual images directly of daily activity patterns and social reality and literature studies as supporting data. The results showed that the implementation of PTSL policy in Malinau District has not been successful because of the six indicators, only two indicators are considered successful, namely standards, targets, policies and communication between organizations. Human resource indicators, characteristics of implementers, dispositions/attitudes of implementers and social, economic and political conditions have a major influence on the suboptimal implementation of PTSL policies in Malinau District. Limited human resources, characteristics of implementers and dispositions/attitudes of implementers affect the delivery and perspective of the community towards the PTSL program in Malinau Regency.